Making maps. Issue 4 (1st August 2016) - Harkness, Timandra
Abstract : In an extract from her book, Big Data: Does Size Matter?, Timandra Harkness meets data‐based map makers CartoDB to discuss citizen cartographers and the pros and cons of location intelligence Abstract : In an extract from her book, Big Data: Does Size Matter?, Timandra Harkness meets data‐based map makers CartoDB to discuss citizen cartographers and the pros and cons of location intelligence